The wife stalker ebook A novel. - Constantine, Liv (2020)
Soon to be an original movie on Lifetime, premiering March 29! The bestselling author of The Last Mrs. Parrish—a Reese Witherspoon Book Club pick—returns with a psychological thriller, filled with chilling serpentine twists, about a woman fighting to hold onto the only family she's ever loved—and how far she'll go to preserve it. Named one of the most anticipated thrillers of the year by Goodreads, Bustle, SheReads, and Library Journal; A LibraryReads pick of the month Breezing into the upscale seaside paradise of Westport, Connecticut, gorgeous thirtysomething Piper Reynard sets down roots, opening a rehab and wellness space and joining a local yacht club. When she meets Leo Drakos, a handsome, successful lawyer, the wedding ring on his finger is the only thing she doesn't like about him. Yet as Piper well knows, no marriage is permanent. Meanwhile, Joanna has been waiting patiently for Leo, the charismatic man she fell in love with all those years ago, to re-emerge from the severe depression that has engulfed him. Though she's thankful when Leo returns to his charming, energetic self, paying attention again to Evie and Stelli, the children they both love beyond measure, Joanna is shocked to discover that it's not her loving support that's sparked his renewed happiness—it's something else. Piper. Leo has fallen head over heels for the flaky, New Age-y newcomer, and unrepentant and resolute, he's more than willing to leave Joanna behind, along with everything they've built. Of course, he assures her, she can still see the children. Joanna is devastated—and determined to find something, anything, to use against this woman who has stolen her life and her true love. As she digs deeper into Piper's past, Joanna begins to unearth disturbing secrets . . . but when she confides to her therapist that she fears for the lives of her ex-husband and children, her concerns are dismissed as paranoia. Can she find the proof she needs in time to save them?